Efektivitas Strategi Rekrutmen Digital dalam Meningkatkan Kualitas Pelamar di SMA Negeri 9 Mandau: Penelitian - Indra Putra, Mija; Dolayance, Rori; Gustituati, Nurhizrah; Anisah, Anisah; Achyar, Novriyanti (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Digital transformation has reshaped recruitment practices in educational institutions, including secondary schools. SMA Negeri 9 Mandau faces increasing demands to attract qualified teachers and educational staff who align with the school’s academic standards and professional culture. This article examines the effectiveness of digital recruitment strategies in enhancing applicant quality, drawing on a comprehensive review of relevant books, scientific journals, and empirical studies on e-recruitment, employer branding, and competency-based selection. The results of the review indicate that digital recruitment contributes positively to expanding applicant reach, streamlining administrative processes, and improving candidate quality provided that the strategy incorporates clear job information, well-structured digital platforms, competency based assessments, and strong employer branding. The study highlights both opportunities and challenges of digital recruitment in the school context, and offers practical recommendations for SMA Negeri 9 Mandau to maximize the benefits of technology-supported hiring.